Apocalyptic thinking in early Judaism engaging with John Collins' "The Apocalyptic imagination" - Crawford, Sidnie White 1960-; Wassen, Cecilia 1962- (Leiden Boston Brill, 2018)
Front Matter -- Copyright page -- Contributors -- Introduction /Sidnie White Crawford and Cecilia Wassén -- The Apocalypse and the Sage: Assessing the Contribution of John J. Collins to the Study of Apocalypticism /Matthew Goff -- A Dwelling Place of Demons: Demonology and Apocalypticism in the Dead Sea Scrolls /Bennie H. Reynolds III -- End Time Temples in the Dead Sea Scrolls: Expectations and Conflict /Cecilia Wassén -- Situating the Aramaic Texts from Qumran: Reconsidering Their Language and Socio-Historical Settings1 /Daniel Machiela -- The Aramaic Imagination: Incubating Apocalyptic Thought and Genre in Dream-Visions among the Qumran Aramaic Texts1 /Andrew B. Perrin -- Origins of Evil in Genesis and the Apocalyptic Traditions /Ida Fröhlich -- Eschatology and Time in 1 Enoch /Loren Stuckenbruck -- The Ram and Qumran: The Eschatological Character of the Ram in the Animal Apocalypse (1 En. 90:10–13) /Eyal Regev -- Comparative Eschatology: Paul’s Letters and the Dead Sea Scrolls1 /Adela Yarbro Collins -- The End is Not Yet: Concluding Reflections /John J. Collins.
It has been over 30 years since John Collins’ seminal study The Apocalyptic Imagination first came out. In this timely volume, Apocalyptic Thinking in Early Judaism: Engaging with John Collins’ The Apocalyptic Imagination , leading international experts of Jewish apocalyptic critically engage with Collins’ work and add to the ongoing debate with articles on current topics in the field of apocalyptic studies. The subjects include the genre and sub categories of apocalypses, demonology, the character of dream visions, the books of Enoch, the significance of Aramaic texts, and apocalyptic traditions in the Dead Sea Scrolls as well as in Paul’s writings. The volume ends with Collins’ response to the articles
Online-Ausg.
Keywords: Collins, John J -- 1946-; Collins, John J -- 1946-; Apocalyptic Literature -- History and criticism; Apocalyptic Literature -- History and criticism; Aufsatzsammlung